2010
DOI: 10.1039/b914015h
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of oxygen condition in the Ria Formosa coastal lagoon, Portugal

Abstract: Dissolved oxygen (DO) is one of the most important environmental variables of water quality, especially for marine life. Consequently, oxygen is one of the Chemical Quality Elements required for the implementation of European Union Water Framework Directive. This study uses the example of the Ria Formosa, a meso-tidal lagoon on the south coast of Portugal to demonstrate how monitoring of water quality for coastal waters must be well designed to identify symptoms of episodic hypoxia. New data from the western e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Herein, the levels of DO were always higher than 8 mg L −1 , even in summer when average temperatures are very high (>25°C), and so the hypoxia described in previous studies (Newton et al 2010) was never observed in the present one. Unfortunately, the other parameters strongly proved that the water quality of the Ria Formosa Lagoon was worse in 2010 than reported in the past (Falcão et al 2003).…”
Section: Physico-chemical Datamentioning
confidence: 64%
See 1 more Smart Citation
“…Herein, the levels of DO were always higher than 8 mg L −1 , even in summer when average temperatures are very high (>25°C), and so the hypoxia described in previous studies (Newton et al 2010) was never observed in the present one. Unfortunately, the other parameters strongly proved that the water quality of the Ria Formosa Lagoon was worse in 2010 than reported in the past (Falcão et al 2003).…”
Section: Physico-chemical Datamentioning
confidence: 64%
“…We hypothesize that such compounds do exist and reach biologically significant amounts in the lagoon waters. Despite the high water turnover at each tide, several studies reported eutrophication and hypoxia, mainly in summer at some spots of the lagoon (Newton and Mudge 2005;Newton et al 2010); however, no information exists about the presence of either phytoestrogens or the annual fluctuation patterns of sitosterol. These compounds in spite of being of natural/vegetal sources, in high amounts phytoestrogens and sitosterol, are known to act as endocrine disrupter compounds (EDCs; Hoerger et al 2009;Clotfelter et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…As to the physic-chemical parameters of the water, a pH higher than expected (>8.2) was detected in Salgados and Dunas Douradas lagoons, although this did not reveal to be exclusive of mosquito larval presence, as these were detected in Salgados, which had the highest pH registered. The levels of dissolved oxygen measured were always above 5 mg/l, at around noon time, which could indicate much lower levels in the night and dawn as observed in this coastal system (Newton et al, 2010). Furthermore, in the lagoons Garrão and Dunas Douradas, the ichthyofauna was inexistent in 2007 probably due to anoxia in the water and lack of communication with the sea, and high mortality was observed in the Salgados lagoon (CCDR, 2007).…”
Section: Discussionmentioning
confidence: 65%
“…The knowledge of the seasonal residence time provides valuable information regarding both biological and chemical processes on coastal systems. In the scope of this research, the combination of several physical parameters was accessed to understand its impact on the physico-chemical properties of both estuaries, specifically DO, as one of the most important environmental variables of water quality [48].…”
Section: Water Timescales Effect On the Do Variabilitymentioning
confidence: 99%